Chick Lit as Postfeminist Disintegrated Sisterhood in Jennifer Weiner’s In Her Shoes - Al-Farttoosi , Tahseen Ali Mhodar (International Journal of Psychosocial Rehabilitation, 2020)
This article examines Jennifer Weiner’s In Her Shoes as a Chick Lit novel. Chick Lit features are represented in one postfeminist characteristic. i.e., that is the focus on the individual instead of a collective sisterhood. Individual sisterhood illustrates prolific productions in feminist discourses which are multiple, contradictory, and overlap in their femininity consumerism. Some of the post-feminist premises have sometimes been exalted for being pro-feminist, while others for being anti-feminism because of celebrating an indeterminate subjectivity. The focus of this study, therefore, sheds light on the depiction of the devilish female character. Devilishness is an attribute of body appearance used in order to bridge certain psychological gaps, by substituting subjective identity which is exclusionary and perpetuates society’s traditional mentality. With an activist postfeminist discourse, the object is (body aspects) centered. To explore those aspects of postfeminists’ preoccupation with objective categories of female identity and its perpetual longing to affirm a personal subjectivity, the feeling of constant attrition will be studied. The final obliteration of female identity and its inclusive human aspects permeates the long inherited feminist code concerning women and their archetypal inferiority to men. This article, therefore, scrutinizes the myth of traditional devil women perceived by patriarchal thinking in Weiner’s In Her Shoes. Women’s devilishness is symbolically highlighted through the novel’s postfeminism’s proliferate obsession with the extrinsic features of body leading to ironic self- discovery and consequently self-expression to efface women devilish identity. This characteristic is represented in Maggie’s devilish character caused by society and the abandonment of sisters.